Everyday vulnerabilities – money laundering through cash intensive businesses. Issue 3 (6th July 2015) - Gilmour, Nicholas; Ridley, Nick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide an understanding of the specific techniques through which illicit funds generated by criminals are moved, transferred and laundered in the financial arrangement retained by cash-intensive businesses in the UK and internationally. Design/methodology/approach – This paper presents exploratory findings from research conducted between 2011 and 2013 in the UK. The research undertaken sought to identify the process, steps and vulnerabilities behind money laundering via cash-intensive businesses and highlight the explicit facilitators to enable this method of money laundering to take place. Findings – Despite significant research into money laundering typologies, the use of cash couriers and cash-intensive businesses has remained largely untouched regardless of the increased implementation of anti-money laundering (AML) policies and procedures seeking to halt the depositing of illicit cash into the global financial system. This paper demonstrates how cash-intensive businesses are extremely vulnerable to money laundering, despite the large-scale AML efforts focused on combating money laundering across a broad range of sectors. Research limitations/implications – This paper is of value to government policymakers, regulators and financial institutions considering future preventative measures. It is also of value to financial investigators and law enforcement agencies intent on investigating money laundering. While the paper relies on data from the UK, the overall findings are such that wherever cash-intensive businesses exist, so too does the opportunity for money laundering through the financial arrangement retained by such businesses. Originality/value – This paper presents new research on the direct link existing between cash-intensive businesses and money laundering in the UK, despite significant research having previously taken place to identify and develop money laundering typologies.